Comparison of the Effects of Various Blood Plasma Expanders on Platelet Adhesiveness - Schneider, J. A; Sanbar, S. S; Zweifler, A. J (Thrombosis and Haemostasis, 1970)
In 30 non-anesthetized rabbits, platelet adhesiveness of arterial blood was determined before and 2, 6, and 24 h after 10 min intravenous infusions of either 20 ml isotonic saline solution (5 control rabbits), or 2.4 g each of dextran 40,000 (4 rabbits), dextran 70,000 (4 rabbits), polyvinylpyrrolidone (P. V. P.) 40,000 (8 rabbits), hydroxyethyl starch (H. E. S.) 60,000 (4 rabbits), or H. E. S. 450,000 (5 rabbits) in saline solution.Platelet adhesiveness did not change significantly after infusions of saline, dextran 40,000, or H. E. S. 450,000. In contrast, dextran 70,000 and H. E. S. 60,000 promptly produced about one-third decrease in platelet adhesiveness which returned toward control levels 24 h after the infusions. Finally, P.V.P. also promptly diminished percent platelet adhesiveness by about one-third of control values and this effect persisted 24 h after infusion. Changes in platelet adhesiveness did not correlate with alterations in hematocrit or platelet count.On a weight basis, P. V. P. elicits the most persistent decrease in platelet adhesiveness.